National report on the status of women in the British Virgin Islands - Banks-Devonish, Linda M. ([The Committee] TortolaVG, 1994)
Reviews and appraises the status of women in pre- and post-1980s at the national level. Reviews and appraises international support. Looks at future strategic goals and objectives and corresponding financial arrangements.